Secretory CAZymes profile and GH19 enzymes analysis of Corallococcus silvisoli c25j21 - Zhou, Xiaoli; Zhou, Xianmin; Zhang, Xianjiao; Dong, Honghong; Dong, Yijie; Zhu, Honghui (Frontiers in Microbiology, 2024)
Extracellular enzymes play important roles in myxobacteria degrading macromolecules and preying on other microorganisms. Glycoside hydrolases 19 (GH19) are widely present in myxobacteria, but their evolution and biological functions have not been fully elucidated. Here we investigated the comparative secretory proteome of Corallococcus silvisoli c25j21 in the presence of cellulose and chitin. A total of 313 proteins were detected, including 16 carbohydrate-active enzymes (CAZymes), 7 of which were induced by cellulose or chitin, such as GH6, GH13, GH19, AA4, and CBM56. We further analyzed the sequence and structural characteristics of its three GH19 enzymes to understand their potential functions. The results revealed that myxobacterial GH19 enzymes are evolutionarily divided into two clades with different appended modules, and their different amino acid compositions in the substrate binding pockets lead to the differences in molecular surface electrostatic potentials, which may, in turn, affect their substrate selectivity and biological functions. Our study is helpful for further understanding the biological functions and catalytic mechanisms of myxobacterial CAZymes.